Investigation on flax/kevlar hybrid with polylactic acid laminated composites by inclusion of nanoclay and graphene - Abdul Laziz, A'liya (2021)
Due to the low mechanical properties of the natural fiber, hybridisation of flax and kevlar may benefits the use of only single fiber in improving the mechanical properties of the composite materials. Furthermore, inclusion of sufficient amount of nanofillers such as graphene or nanoclay in a fiber reinforced polymer composite can aid to improve the flexural and impact properties of the composite. In this research, hybrid flax/kevlar fibre composite reinforced with PLA composites have been prepared by using hot press technique. Initially, the flax fibre were treated with 2 % of sodium hydroxide (NaOH) solution. Nanoclay and graphene were sonicated separately at designated concentration with chloroform and then stirred together with PLA pellet to produce a thin film. The main objectives of this research is to investigate the properties hybrid fibre laminated composites with addition of nanofillers. The specific objectives focused on the investigation of flexural properties of the hybrid laminated nanocomposites with presence of different nanofillers loading. Next, investigate different impact energy of low velocity impact response on the hybrid laminated nanocomposites and finally to analyse the failure morphology of hybrid laminated nanocomposites. Flexural test revealed improvement in strength. Flax/kevlar/PLA nanocomposite filled with 1 wt.% of nanofiller shows improvement in flexural strength of about 13.38 and 8.67 %, for nanoclay and graphene compared to composite without nanofillers. From scanning electron microscope (SEM) images, rough fractured surface was identified from the flexural failure, which due to the slow spreading crack and high energy absorption of the flax/kevlar/PLA composite to resist failure. Impact tests at 10 and 20 J of impact energy for the flax/kevlar/PLA nanocomposite shows incomplete punching holes at the bottom surface layers while complete penetration was found for the flax/kevlar/PLA nanocomposite during impact energy level at 30J. Inclusively, addition of nanofillers improve the mechanical properties up to 1 wt.% while increasing it over 3 wt.% will decrease the properties of composites.